1998
DOI: 10.1074/jbc.273.46.30295
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Glucuronyltransferase Involved in the Biosynthesis of the HNK-1 Epitope on Glycoproteins from Rat Brain

Abstract: The glucuronyltransferase involved in the biosynthesis of the HNK-1 epitope on glycoproteins was purified to an apparent homogeneity from the Nonidet P-40 extract of 2-week postnatal rat forebrain by sequential chromatographies on CM-Sepharose CL-6B, UDP-GlcASepharose 4B, asialo-orosomucoid-Sepharose 4B, Matrex gel Blue A, Mono Q, HiTrap chelating, and HiTrap heparin columns. The purified enzyme migrated as a 45-kDa protein upon SDS-polyacrylamide gel electrophoresis under reducing conditions, but eluted as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Under these assay conditions, the bacterially expressed FLAG-Pcat and FLAG-Scat exhibit the specific activities of about 1,100 and 450 nmol/min/mg protein, respectively (17). The specific activities were comparable with that of GlcAT-P purified from rat brain (9). As shown in Fig.…”
Section: Effect Of the Interaction On The Glucuronyltransferase And Ssupporting
confidence: 55%
“…Under these assay conditions, the bacterially expressed FLAG-Pcat and FLAG-Scat exhibit the specific activities of about 1,100 and 450 nmol/min/mg protein, respectively (17). The specific activities were comparable with that of GlcAT-P purified from rat brain (9). As shown in Fig.…”
Section: Effect Of the Interaction On The Glucuronyltransferase And Ssupporting
confidence: 55%
“…The GlcAT-D expression pattern was slightly different from that of GlcAT-P. GlcAT-D transcripts were positive in the pallidum and retina where GlcAT-P expression was not specifically observed, suggesting different in vivo functions between the two GlcATs. GlcAT-D had catalytic activity on both glycoprotein and glycolipid acceptors in our in vitro assay, whereas GlcAT-P was reported to be active on only glycoprotein acceptors (20). This may reflect different localization patterns of the GlcATs, where the GlcAT-D is expressed in a wider region than GlcAT-P.…”
Section: Fig 10 Hplc Analysis Of Smith Degradation Productsmentioning
confidence: 48%
“…The present study showed that GlcAT-D acts on both glycoprotein and glycolipid acceptors in vitro, whereas GlcAT-P has been reported to be specific to glycoprotein acceptors (20,35). It remains to be determined what these glucuronyltransferases use as acceptor substrates in the nervous system.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations